2013
DOI: 10.3109/09637486.2013.845650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary eugenol on xenobiotic metabolism and mediation of UDP-glucuronosyltransferase and cytochrome P450 1A1 expression in rat liver

Abstract: Xenobiotic-metabolizing enzymes (XMEs) play an important role in the elimination and detoxification of xenobiotics and drugs. A variety of natural dietary agents are known to protect against cancer by inducing XME. To elucidate the molecular mechanism of XME induction, we examined the effect of dietary eugenol (4-allyl-1-hydroxy-2-methoxybenzene) on xenobiotic metabolism. In this study, rats were administered dietary eugenol for 4 weeks to investigate the various effects of UDP-glucuronosyltransferase (UGT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The results of this and our previous preclinical rodent model studies confirmed our scientific assumption that the significant anticancer effect of whole plant functional foods is based more on a combination of several phytochemicals than on isolated molecules [2][3][4][5][6][7]39,40]. Numerous papers describe that dominant metabolites found in our EOC (cinnamaldehyde, eugenol, linalool, eucalyptol, limonene) are absorbed via rat GIT and are consequently significantly effective in the organism [41][42][43][44][45]. There is no reason to doubt that dominant metabolites from EOC were present in rat plasma after eating cinnamon in this study.…”
Section: Discussionsupporting
confidence: 78%
“…The results of this and our previous preclinical rodent model studies confirmed our scientific assumption that the significant anticancer effect of whole plant functional foods is based more on a combination of several phytochemicals than on isolated molecules [2][3][4][5][6][7]39,40]. Numerous papers describe that dominant metabolites found in our EOC (cinnamaldehyde, eugenol, linalool, eucalyptol, limonene) are absorbed via rat GIT and are consequently significantly effective in the organism [41][42][43][44][45]. There is no reason to doubt that dominant metabolites from EOC were present in rat plasma after eating cinnamon in this study.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, clove may represent a novel therapeutic herb for the treatment of colorectal cancer, and oleanolic acid was one of the components in ethyl acetate extract of cloves responsible for its antitumor activity [231]. Similarly, eugenol also contributed to treatment against liver cancer [232]. …”
Section: Other Spicesmentioning
confidence: 99%
“…Essential oils extracted from cloves contain eugenol as their primary component. In spite of eugenol's increasing medicinal use, there are few studies investigating its interactions with CYP enzymes ( Gardner et al, 1997 , Iwano et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%